Upaya Pencegahan Stunting Ditinjau dari Intervensi Gizi Spesifik Pada Masa 1000 Hari Pertama Kehidupan di Wilayah Kerja Puskesmas Pasar Simpang Kabupaten Tanggamus - Ratnasari, Yuni; Nurhandayani, Tria (Universitas Serang Raya, 2024)
This research aims to describe the implementation of the role of Community Health Centers in efforts to prevent stunting through specific nutritional interventions during the 1000 HPK period and identify supporting and inhibiting factors in implementing the role of Pasar Simpang Community Health Center, Kota Agung Timur District, Tanggamus Regency in preventing stunting. This research used a purposive sampling technique so that the subjects of this research were the Pasar Simpang Community Health Center, the Tanggamus District Health Service, Village Midwives, Pekon officials, and the community in the working area of the Pasar Simpang Community Health Center. The results of this research show the implementation of the role of Community Health Centers through specific nutritional interventions during the 1000 HPK period, namely: 1) Providing additional food for KEK pregnant women, 2) Supplementation of blood supplement tablets, 3) Promotion and counseling on breastfeeding, 4) Promotion and counseling on feeding infants and children, 5) Management of malnutrition, 6) Providing additional recovery food for underweight children, 7) Monitoring and promoting growth. The implementation of the role of Community Health Centers in preventing stunting cannot be separated from several supporting factors, including support from related parties, namely the Tanggamus District Health Service and NGOs, as well as integrative coordination and collaboration. However, there are several inhibiting factors in implementing the role of community health centers, namely, limited PMT assistance, the COVID-19 pandemic situation, low awareness of community behavior, and socio-economic and socio-political factors.